Legal Politics in Land Acquisition for the Waru-Buduran Frontage Road in Sidoarjo Regency, Indonesia - Azizah, Putri; Suhadi, Suhadi; Wahanisa, Rofi (Faculty of Sharia and Law, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Land occupies a strategic position within Indonesia’s legal system, functioning not only as an economic asset but also as a social instrument intended to achieve the greatest prosperity of the people, as mandated by Article 33 paragraph (3) of the 1945 Constitution of the Republic of Indonesia. In the context of infrastructure development, the implementation of social functions of land frequently necessitates land acquisition for public purposes, particularly in transportation projects aimed at reducing traffic congestion and enhancing public welfare. This study aims to analyze land acquisition for the construction of the Waru–Buduran Frontage Road in Sidoarjo Regency, examining its legal basis, governing principles, and underlying legal-political orientation. The research employs a normative juridical method, utilizing statutory and conceptual approaches, supported by empirical data on the implementation of land acquisition at the research site. The findings reveal that the land acquisition process for the Waru–Buduran Frontage Road has been conducted in accordance with the applicable legal framework, particularly Law Number 2 of 2012 on Land Acquisition for Development in Public Interest and its implementing regulations, and is guided by principles of humanity, justice, utility, and legal certainty. Furthermore, policy reflects the local government’s legal politics aimed at accelerating infrastructure development and alleviating traffic congestion while ensuring protection of affected landowners’ rights through fair and adequate compensation. The implications of this study underscore the importance of enhancing public participation, enhancing transparency in compensation valuation, and ensuring the consistent application of land acquisition principles to achieve effective infrastructure development that remains aligned with the rule of law and social justice.